Subsistence and persistence: agriculture in the Central Plains of China through the Neolithic to Bronze Age transition. (August 2020) - Jing, Yuan; Campbell, Roderick; Castellano, Lorenzo; Xianglong, Chen
Abstract: Abstract : The Neolithic to Bronze Age transition ( c . 5000–3500 BP) saw dramatic socio-economic developments in ancient China. Complex polities emerged in many regions, only to decline and collapse by the end of the period. In the Central Plains area, however, these centuries laid the foundations for China's first dynasties. This article presents zooarchaeological, palaeobotanical and isotopic research from key sites of the Central Plains spanning the period c . 5000–3500 BP. The results demonstrate that, contrary to narratives of the climate-induced collapse of these polities, Central Plains agricultural regimes intensified and diversified during the Neolithic to Bronze Age transition.